Design of Interactive Health Promotion Portal Prototype at House of Health Promotion TeFa - Prakoso, Bakhtiyar Hadi; Vestine, Veronika; Suyoso, Gandu Eko Julianto (International Journal of Health and Information System, 2024)
TeFa House of Health Promotion at Polije is a Teaching Factory that is currently initiated by the Health Department's Health Promotion study program. This TeFa serves as a platform for health communication, information, and education, as well as a space for research and the dissemination of research findings by faculty and students. Based on the conducted situation analysis, TeFa Health Promotion House currently lacks integration of communication, information, and education media into health promotion activities. This deficiency leads to suboptimal management of health media content. The aim of this research is to create a web portal design for this problem. The method used to develop this portal design is the User-Centered Design method. The results of testing and design analysis conclude that the portal design developed aligns with user expectations. The main features include Articles, Consultations, Videos, Audio, and Polls. For further research, the design can be expanded into an application